Influence of Metal Fragment Mobility and Solution Dynamics on Cationic Rearrangements in Multimetallic Alkoxide Frameworks. Issue 1 (2nd January 2018) - Hegemann, Corinna; Heidemann, Tim; Pantenburg, Ingo; Mathur, Sanjay
Abstract: Multimetallic alkoxides show manifold dynamics in solution comprising ligand switching among different sites (terminal, doubly or triply bridging), coordination lability of alkoxometallate units (M(OR)x − ) and rearrangement of metal centers. Solution behavior and structural investigations of heterobimetallic iodide isopropoxides [IMCe2 (OPr i )9 ]2 (M=Cd (1 ), Ba (2 )) and corresponding potassium alkoxometallates of Sr and Al revealed equilibrium of several interconverting species that rearrange to form stable monomeric or dimeric trimetallic frameworks. Quantitative formation of dimeric heterotrimetallic alkoxides [Cd(OPr i )3 SrCe2 (OPr i )9 ]2 (3 ), [Cd(OPr i )3 BaCe2 (OPr i )9 ]2 (4 ) and monomeric [Al(OPr i )4 (HOPr i )BaCe2 (OPr i )9 ] (5 ) confirmed the tendency of metallo‐fragments to rearrange themselves for achieving the maximum possible coordination number for constituent metals. Multinuclear NMR spectroscopy, elemental analysis, mass spectrometry and X‐ray diffraction analyses verified the potential of electronically and sterically unsaturated alkoxometallate units in initiating the redistribution of metal centers. Abstract : The challenge of rationally constructing heterotermetallic alkoxides can be addressed by adjusting the chemical configuration (ligating ability) and reactivity (propensity to achieve higher coordination numbers) of the appropriate alkoxometallate (M(OR)n − ) units. Whereas Ce IV 2 (OPr i )9 − unit acts as a sequestering agent to endow stability to the triangular heterobimetallic "M II M IV 2 " framework, the highly reactive M(OR3 ) − units based on larger alkaline earth metals can induce an interesting metal exchange revealing the unusual dynamics active in the solution, which often go unnoticed in NMR studies due to highly fluxional behavior of polymetallic alkoxides.